Information sharing and banking efficiency in Africa: A disaggregated panel data analysis - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2022)
The study assesses the how information sharing by means of mobile phones affects banking system efficiency in Africa with particular emphasis on income levels (Middle income versus Low income countries) and legal origins (English Common law versus French Civil law countries). The focus is on 53 African countries with data for the period 1996-2019 and the empirical evidence is based in Quantile regressions which enable the study to assess the nexus throughout the conditional distribution of banking system efficiency. The following findings are established: (i) mobile phone penetration promotes banking system efficiency in the 25th quantile and the median of banking system efficiency in low income countries while for middle income countries; it is significant exclusively in the bottom quantile (i.e. 10th quantile). (ii) With the exception of the highest (i.e. 90th) quantile in which the effect of the mobile phone is not significant in English Common law countries, the impact is significant throughout the conditional distribution of banking system efficiency in Common law countries. (iii) As for French Civil law countries, the nexus is only significant in the median and highest (i.e. 90th) quantile of the conditional distribution of banking system efficiency. Policy implications are discussed.
Keywords: G20; G29; L96; O40; O55; 330; Allocation efficiency; Information asymmetry; Mobile phones